Experimental Enhancement for Electric Properties of Polyethylene Nanocomposites under Thermal Conditions - Ahmed Thabet; Youssef Mobarak (Advances in Electrical and Electronic Engineering, 2017)
Polymer properties can be experimentally tailored by adding small amounts of different nanoparticles for enhancing their mechanical, thermal and electrical properties. The work in this paper investigates enhancing the electric and dielectric properties of Low Density Polyethylene (LDPE), and High Density Polyethylene (HDPE) polymer materials with cheap nanoparticles. Certain percentages of clay and fumed silica nanoparticles are used to enhance electric and dielectric properties of polyethylene nanocomposites films. By using the Dielectric Spectroscopy; the electric and dielectric properties of each polyethylene nanocomposites have been measured with and without nanoparticles at various frequencies up to 1kHz under different thermal conditions (20°C and 60°C). And so, we were successful in specifying the optimal nanoparticles types and their concentrations for the control of electric and dielectric characterization.